A Surprise Out of Zion? Case Studies in Israel's Decisions on Whether to Alert the United States to Preemptive and Preventive Strikes, from Suez to the Syrian Nuclear Reactor - Bass, Warren (RAND Corporation, 2015)
Might U.S. officials be surprised by an Israeli strike on Iran's nuclear facilities? This study examines key historical precedents, considering four cases in which Israeli leaders chose preemptive or preventive military strikes and had to decide whether to notify or consult with the United States: the Suez crisis of 1956, the Six-Day War of 1967, the 1981 strike on Iraq's nuclear reactor, and the 2007 bombing of Syria's al-Kibar nuclear facility.